2014
DOI: 10.1016/j.socscimed.2013.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Social relationships and healthful dietary behaviour: Evidence from over-50s in the EPIC cohort, UK

Abstract: Social relationships are an important aspect of a person's social environment that can protect against a wide range of chronic conditions and facilitate recovery from disease. Social relationships have also been linked to dietary behaviour which may be an important pathway through which social circumstances exert their influence on health. Yet, questions remain about which structural aspects of social relationships most affect healthful dietary behaviours and whether different structural components interact to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
154
4
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(179 citation statements)
references
References 58 publications
16
154
4
5
Order By: Relevance
“…Observational study results demonstrated lower vegetable scores for both widowed men and women, compared to partnered people. Widowed men's vegetable scores were almost half those of widowed women's, and men's' dietary patterns overall were more negatively affected than those of women in regard to living alone, being un-partnered and having limited contact with friends (Conklin et al, 2013). Place of residence may also be associated with marital status and dining companions.…”
Section: Social Wellnessmentioning
confidence: 91%
See 3 more Smart Citations
“…Observational study results demonstrated lower vegetable scores for both widowed men and women, compared to partnered people. Widowed men's vegetable scores were almost half those of widowed women's, and men's' dietary patterns overall were more negatively affected than those of women in regard to living alone, being un-partnered and having limited contact with friends (Conklin et al, 2013). Place of residence may also be associated with marital status and dining companions.…”
Section: Social Wellnessmentioning
confidence: 91%
“…Authors suggest that limited social contact may be an independent risk factor for poorer dietary pattern quality (Sahyoun & Zhang, 2005). In contrast, weekly family contact (instead of daily) was more positively associated with vegetable variety in women from the European Prospective Investigation of Cancer (EPIC) study (Conklin et al, 2013). Perhaps this is a result of older women feeling that they are monitored by family members when they are checked on daily, versus feeling a more social nature in onceper-week interactions.…”
Section: Social Wellnessmentioning
confidence: 92%
See 2 more Smart Citations
“…Also, very little is known about relationship between diet/DP and health and bio-psycho-social factors in this age group. Specifically, diet quality has been linked to socioeconomic status defined either by education, social class (occupation) and income in general and older adults populations (aged 60 and over) (56)(57)(58) , but to which extent and which dimension socioeconomic status plays a role in diet characteristics in very late life is not known. Utilising dietary data collected by 24-h multiple-pass dietary recalls from participants in the Newcastle 85+ study (16,17,34) and two-step clustering, we identified three distinct DP, which differed with respect to the key sociodemographic, lifestyle, health and functioning measures (59) .…”
Section: Dietary Patterns and Health In The Very Oldmentioning
confidence: 99%